1989
DOI: 10.1093/cvr/23.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes on metabolic coronary dilatation in the rat

Abstract: There is increasing evidence that patients with diabetes mellitus are prone to ischaemic heart disease. This study examined cardiac hyperactivity and its consequent metabolically induced coronary dilatation in isolated, perfused, electrically paced rat hearts from control and spontaneously diabetic Bio-Breeding (BB) rats. Cardiostimulation produced by noradrenaline, calcium, or by tachycardia elicited increases in coronary flow that were significantly lower in diabetic hearts. However, the inotropic responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
1
18
1
Order By: Relevance
“…The current results are in contrast with several observations in animal models for diabetes [9,10] that studied the responsiveness of the heart and coronary vasculature to adenosine. We cannot exclude the possibility that diabetes mellitus differentially affects the coronary and forearm vascular bed in humans.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current results are in contrast with several observations in animal models for diabetes [9,10] that studied the responsiveness of the heart and coronary vasculature to adenosine. We cannot exclude the possibility that diabetes mellitus differentially affects the coronary and forearm vascular bed in humans.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, an impaired responsiveness to the vasodilator effect of adenosine has been observed in animal models of diabetes mellitus [9,10]. Several mechanisms may be responsible for this reduced responsiveness to adenosine.…”
Section: Introductionmentioning
confidence: 99%
“…Such an impairment of metabolic microvascular coronary vasodilation as been shown in diabetic rat hearts (19) and in diabetic patients in response to atrial pacing by Nasher et al (3). However, in the latter study, other coronary risk factors that could impair microvascu- CPT and coronary vasomotion.…”
Section: Discussionmentioning
confidence: 68%
“…Several animal and human studies have shown that coronary metabolic vasodilation is impaired in diabetes. In diabetic rats, coronary blood flow increase in response to norepinephrine infusion and to pacing was significantly lower than that in control rats (26). In diabetic dogs, coronary arterioles did not dilate when coronary perfusion pressure was decreased (27).…”
Section: Discussionmentioning
confidence: 76%